Engineering Islets From Stem Cells: The Optimal Solution for the Treatment of Diabetes? - Du, Suya; Li, Yanjiao; Geng, Zhen; Zhang, Qi; Buhler, Leo H.; Gonelle-Gispert, Carmen; Wang, Yi (Frontiers in Immunology, 2022)
Diabetes is a metabolic disease characterized by insulin deficiency. Bioengineering of stem cells with the aim to restore insulin production and glucose regulation has the potential to cure diabetic patients. In this review, we focus on the recent developments for bioengineering of induced pluripotent stem cells (iPSCs), mesenchymal stem cells (MSCs), embryonic stem cells (ESCs), and pancreatic progenitor cells in view of generating insulin producing and glucose regulating cells for β-cell replacement therapies. Recent clinical trials using islet cells derived from stem cells have been initiated for the transplantation into diabetic patients, with crucial bottlenecks of tumorigenesis, post-transplant survival, genetic instability, and immunogenicity that should be further optimized. As a new approach given high expectations, bioengineered islets from stem cells occupies considerable potential for the future clinical application and addressing the treatment dilemma of diabetes.